On the Fekete-Szegö problem - B. A. Frasin; Maslina Darus (International Journal of Mathematics and Mathematical Sciences)
Let f(z)=z+a2z2+a3z3+⋯ be an analytic function in the open unit disk. A sharp upper bound is obtained for |a3−μa22| by using the classes of strongly starlike functions of order β and type α when μ≥1.